Virulence gene profiling of enterohemorrhagic (EHEC) and enteropathogenic (EPEC) Escherichia coli strains: a basis for molecular risk assessment of typical and atypical EPEC strains - Bugarel, Marie (BioMed Central, 2011)
BACKGROUND: Enterohaemorrhagic E. coli (EHEC) can cause severe disease such as bloody diarrhoea and haemolytic uraemic syndrome in humans. Besides production of Shiga toxins, the presence of LEE (eae-gene) and non-LEE (nle) encoded effector genes harboured on O-islands OI-122, OI-71 and OI-57 is associated with EHEC virulence and their frequency in outbreaks. Genes encoded by the EHEC-plasmid are putative virulence markers of EHEC. EHEC-plasmids, LEE and non-LEE effector genes have also been detected in some strains of enteropathogenic E. coli (EPEC). The objective of this study was to analyze the relationship between EHEC and EPEC for virulence genes encoded by genomic O-islands and by the EHEC-plasmids. RESULTS: Nle genes ent/espL2, nleB and nleE (OI-122), nleA, nleF and nleH1-2 (OI-71), nleG5-2 and nleG6-2 (OI-57), espK (CP-933N) and the EHEC-plasmid encoded genes ehxA, espP, etpD and katP were searched in 73 typical and in 235 atypical enteropathogenic E. coli (EPEC) strains. Typical and atypical EPEC each fall into two clusters. Cluster 1 typical (n = 46) and atypical (n = 129) EPEC strains were characterized by the presence of OI-122 encoded genes and grouped together with 64 investigated EHEC strains. Cluster 2 typical (n = 27) and atypical (n = 106) strains grouped together with 52 LEE-negative, Shiga toxin-producing E. coli (STEC) and with 21 apathogenic E. coli strains. Typical EPEC Cluster 1 strains belonged to serotypes frequently involved in severe illness and outbreaks in children (O111:H2, O114:H2, O55:H6, O127:H6 and O142:H6). Atypical EPEC Cluster 1 strains were characterized by serotypes related to EHEC (O26:H11, O55:H7, O145:H28, O103:H2 and O103:H25). CONCLUSION: The OI-122 encoded nleB gene was found to be most closely associated with Cluster 1 strains and may serve as a diagnostic tool for the identification of virulent EHEC and EPEC seropathotypes. OI-71 encoded genes nleA, nleF and nleH1-2 are less associated with Cluster 1 strains. EHEC-plasmid, OI-57 and CP-933 associated genes showed only weak similarities with virulent Cluster 1 EHEC and EPEC strains.